Meeting refugees on Instagram: Platformisation of news and knowledge production about refugees in digital social space - Bagas Aditya; Sumini (Digital Geography and Society, 2025)
Refugees are figures whose identities are socially and politically perceived and constructed. However, the mechanisms by which this construction persists in digital space are inadequately explored. This study aims to investigate the process of knowledge production about refugees in the digital social space, Instagram. A digital ethnography was conducted on an Instagram news aggregator, combining discourse analysis, visual analysis of 121 posts, and an interview with the account administrator to explore how the Rohingya are represented and how knowledge about them is constructed on the platform. Findings highlight that knowledge production builds upon the mechanism of platformisation of news and networked knowledge-sharing, which is also influenced by platform affordances. Rather than playing as a passive medium, Instagram acts actively by being involved in the socio-political processes of framing narratives about refugees by recommending or limiting specific narratives. A socio-technical process emerges through this interaction between the platform and human agencies, shaping refugee identities in a way that fosters decentralised knowledge production yet lacks accuracy. This study provokes further exploration of digital geography, particularly in the context of digital meaning-making of vulnerable groups and its implications for public attitudes toward refugees in real life.